RCEV heteroscedasticity test based on the studentized residuals - Celik, Resit (TAYLOR & FRANCIS INC, 2019)
All the usual heteroscedasticity tests in the statistics and econometrics literature are based on raw residuals. Although the raw residuals are heteroscedastic, studentized residuals can still be homoscedastic. In this study, the version of celik's RCEV heteroscedasticity test which is based on studentized residuals is introduced.
Keywords: RCEV heteroscedasticity test; monotonic heteroscedasticity; non monotonic heteroscedasticity; centered external variable; DISTRIBUTED RESIDUALS; MODELS; Mathematics